Daytech anti-theft burglar wireless security with monitoring enhanced app - Yusaini, Muhammad Syamim; Sidik, Norbaiti; Mohamad, Sufian; Mohd. Atan, Fadila (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
The Daytech Anti-Theft Burglar Wireless Security System With Monitoring Enhanced App is an IoT-enabled solution designed to enhance home security by integrating reliable sensors, a microcontroller, and a smartphone application. The system employs an ultrasonic sensor to monitor specific areas, such corridor, and alert users of motion or any presence in real- time. Upon detection, it activates recording and notifies the owner through online. Magnetic reed switches monitor unauthorized access points, such as doors and windows for any attempted break-ins. This cost-effective and scalable solution addresses gaps in traditional security systems by offering local real-time monitoring and user-friendly features. By ensuring enhanced safety and control, the system contributes to a more secure and sustainable living environment